2016
DOI: 10.1136/oemed-2016-103569
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal examination of temporality in the association between chronic disease diagnosis and changes in work status and hours worked

Abstract: Chronic disease can result in work loss following diagnosis. Research is required to understand how modifying occupational conditions may benefit employment immediately after diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…44 As individuals develop more severe chronic conditions, they may be less able to work and generate income. 45 Furthermore, dietary counseling and health education at health care visits may increase awareness of diet recommendations but also inability to afford healthy foods, which lead to an increased perception of food insecurity. 9 Among participants with self-reported diabetes and hypertension, food insecurity was not associated with measures of inadequate disease control.…”
Section: Discussionmentioning
confidence: 99%
“…44 As individuals develop more severe chronic conditions, they may be less able to work and generate income. 45 Furthermore, dietary counseling and health education at health care visits may increase awareness of diet recommendations but also inability to afford healthy foods, which lead to an increased perception of food insecurity. 9 Among participants with self-reported diabetes and hypertension, food insecurity was not associated with measures of inadequate disease control.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients with moderate to severe rheumatoid arthritis, 17% reported changing jobs because of their disease [ 13 ]. In another study, 61.2% with heart disease and 44.5% with arthritis stopped working because of their disease [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Negative changes in patients’ work life can also have important non-financial implications. In other cancer settings, such changes have been linked to a diminished quality of life [ 12 ], psychiatric disorders (eg, depression) [ 13 ], and feelings of a suspension of life and/or normalcy [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among those who are employed, an important role is played by job qualification. Workers undergo fewer diagnostic tests than directors; this is in accordance with the existence of a socio-economic gradient in favour of those occupied in managing position at work [ 26 – 28 ].…”
Section: Discussionmentioning
confidence: 86%